Una visión histórica de las biogeografía dispersionista con críticas a sus fundamentos (2000)
By means of identifying its precursors, fundamental arguments, major proponents, and classic publications, an historical synthesis of the school of dispersalist biogeography is provided. Its concepts and major methods are analyzed and compared  with those of other schools of historical  biogeography. The historical roots of this synthesis emerge from Linnaeus, Buffon, and De Candolle. The founders of a dispersalist school were Darwin, l. vell, and Wallace whose theoretical structure was influenced by the intellectual and social contexts of the 19th century. This structure is recognizable in the neodarwinian biogeography of Darlington, Matthew, Mayr, Simpson and, most recently, Briggs. An ontological and epistemological criticism is provided of dispersalism.